Morphological diversity of Zacatecas Guajillo chile landraces is broad and is given mainly by fruit traits - Amalio Santacruz-Varela, Yolanda del Rocio Moreno-Ramírez; Higinio López-Sánchez, Pedro A. López; González-Hernández, T. Corona-Torres, L. Córdova-Téllez, V. A.; Ortega, Ricardo López- (Emirates Journal of Food and Agriculture, 2019)
Guajillo (Capsicum annuum L.) is one of the five more important chile types used as food in Mexico and the most important to local economy in Zacatecas, whose production is supplied mainly by native populations. In spite of this, not much is known about the morphological diversity of Guajillo landraces of Zacatecas. Here, we describe and quantify their morphological variation in order to establish breeding programs and to preserve the phenotypic diversity. Thirty-two plant, flower, fruit, seed and phenological traits were assessed in 96 Guajillo chile landraces and four improved varities of Guajillo used as controls, grown during the 2015 agricultural cycle in Zacatecas, Mexico. The selection of variables was made based on the analysis of variance and multivariate analysis that were applied to the selected variables to estimate the morphological diversity. A wide variation of plant, fruit and seed characteristics was identified. This morphological heterogeneity is attributed mainly to fruit traits such as: size, weight, shape, color, transverse wrinkling of the fruit, shape of the peduncle and the number of fruits produced. This wide morphological diversity can potentially be utilized in the genetic improvement of Guajillo chile.